(untitled) (Journal of the Bangladesh Agricultural University, 2014)
This paper focuses on conservation agriculture (CA), defined as minimal soil disturbance (no-till) and crop residue retention (mulch) combined with crop rotations. The paper then describes the principles based on which CA runs with briefing suggested improvement on conservation tillage, where no-till, mulch and rotations significantly improve soil properties and other biotic factors. This paper also describes some cons of CA with its future strategies. A Case study from the rice-wheat areas of the Indo-Gangetic Plains of South Asia used to describe how CA practices have been used to raise production sustainably and profitably. Benefits in terms of greenhouse gas emissions and their effect on global warming are also discussed. The paper concludes that agriculture in the next decade will have to sustainably produce more food from less land through more efficient use of natural resources and with minimal impact on the environment in order to meet growing population demands. Promoting and adopting CA management systems can help meet this goal. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19901 J. Bangladesh Agril. Univ. 11(2): 241-248, 2013